Perbedaan Teori Organisme Sel Prokariotik, Eukariotik Dan Virus - Rahmadina Rahmadina; Yulis Aulia; Muhammad Agung Saputra3; Dilla Wardhani; Fitriani Fitriani (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
As the smallest unit of life, a person has the ability to function independently of himself to maintain his survival. The smallest entity that has the ability to reproduce and divide is a cell. The two types of cell architecture are eukaryotic and prokaryotic. Plant cells will also be discussed apart from that. Plant cells will be closed separately even though they are eukaryotic and have special organelles. Every biological process is cellular and controlled. As a result, as long as all basic needs are met, the cell can operate independently. Organisms, or living things, consist of many cells (multicellular) or one cell (unicellular), such as bacteria, archaea, fungi, and protozoa. Viruses are microscopic organisms that exist outside cells. Viruses are obligate parasites because viruses do not have the cellular machinery needed for reproduction, so viruses can only reproduce in living things by entering and exploiting their cells.